ASTRAGALOSIDE IV INHIBITS H2O2-INDUCED APOPTOSIS IN H9C2 CELLS BY ATTENUATING OXIDATIVE STRESS AND MITOCHONDRIAL DAMAGE. (June 2022) - Qi, Miaomiao; Wang, Qiongying; Sun, Runmin; Tian, Li; Yu, Jing
Abstract : Objective: To investigate the effects and mechanisms of As-IV on H2O2-induced apoptosis in H9c2 cells. Design and method: H9c2 cells were divided into three groups, including normal control group (cultured without intervention), H2O2 group (cultured with 200umol/L H2O2 for 2 hours), As-IV group (cultured with 100umol/L As-IV for 1 hour), As-IV with H2O2 group (pretreated with 100umol/L As-IV for 1 hour, then incubated with H2O2 for 2 hours). FITC/PI and DCFH-DA are stained to examine levels of apoptosis and ROS receptively. Levels of SOD and MDA were measured. Stained with JC-1 probe to observe the change of mitochondrial membrane potential (MMP). Western-blot was detected to analyze the expression of Drp-1. Results: 1. The apoptosis rate of H2O2 group ((13.22 ± 3.17 vs 40.55 ± 13.74)%, P < 0.05) was significantly higher than that of control group, which was lower in As-IV with H2O2 group((23.43 ± 4.3 vs 40.55 ± 13.74) %, P < 0.05). 2. The ROS levels were higher in H2O2 group than control group((73.53 ± 5.33 vs 39.02 ± 7.90) %, P < 0.05), which were significant reduced in As-IV with H2O2 group((57.6 ± 4.63 vs 73.53 ± 5.33) %, P < 0.05) Meanwhile, the activity of MDA was increased and the activity of SOD was decreased in H2O2 group compared with that in control group((10.97 ± 0.56 vs 4.85 ± 0.55) nmol/mL, P < 0.05), ((1192.23 ± 341.59 vs 2710.95 ± 274.32)U/L, P < 0.05). Compared with H2O2 group, As-IV with H2O2 group significantly decrease the activity of MDA and increase the activity of SOD ((6.58 ± 0.79 vs 10.97 ± 0.56) nmol/mL, P < 0.05), ((1984.66 ± 188.81 vs 1192.23 ± 341.59) U/L, P < 0.05). 3.MMP was lower and the expression of Drp1 was higher in H2O2 group than that in control group ((0.31 ± 0.01 vs 1.52 ± 0.25) %, P < 0.05), ((0.86 ± 0.003 vs 0.45 ± 0.004) %, P < 0.05). Compared with H2O2 group, MMP was significantly increased and the expression of Drp1 was downregulated ((0.65 ± 0.38 vs 0.31 ± 0.01) %, P < 0.05), ((0.72 ± 0.005 vs 0.86 ± 0.003) %, P < 0.05). Conclusions: As-IV exerts protective effects on H2O2-induced apoptosis by attenuating oxidative stress and mitochondrial damage.